Finite element analysis of corrugated web beams under bending - Chan, C.L.; Khalid, Y.A.; Sahari, B.B.; Hamouda, A.M.S. (Elsevier Science, 2002)
The effect of web corrugation on the beam's strength is presented in this paper. Beams with plane web, vertically and horizontally corrugated webs were investigated using LUSAS finite element package. For the horizontally corrugated case, one arc and two arcs were studied, while half-circular wave corrugation was used for the vertical type. Half of circle corrugations of 22.41 mm mean radius and 3.44 mm thickness were used throughout this study. Non-linear elastic-plastic behaviour has been considered. Three different corrugation radii were taken for each type of the beam to investigate its effect on the beam's strength. Ordinary I-beams, with plane web, were also tested experimentally. The comparison between the results obtained from both methods, for the plane web type, shows 3.1% to 7.1% differences. On the other hand, it is also found that beams with vertically corrugated web stands 38.8% to 54.4% higher moments than the horizontal type. The vertically corrugated web provides a stronger support against the flange buckling, compared to the plane and horizontally corrugated web types. It is found to be the same for the three radii taken. Moreover, corrugated web beams with larger corrugation radius could sustain higher bending moment and it is true for the sizes used throughout this investigation.